An Econometric Analysis of the Investment Attractiveness of Selected European Countries from Japanese Investors' Perspective - Cheba , Katarzyna (Studia Oeconomica Posnaniensia, 2018)
The main purpose of the paper is to assess the investment attractiveness of selected European countries considered from the perspective of Japanese investments in Europe. For many years Japan has been one of the biggest investors in the world. For many years, the Japanese have chosen developed countries with a stable socio-economic situation for their investments. They were very often European countries, indicated as the most competitiveness economy in the world. One can therefore wonder whether there is a relationship between the assessment of the country's competitiveness level and its investment attractiveness in the case of Japanese investors. It should be noted, that a precise distinction between the notions of investment attractiveness and the competitiveness of a region is not an easy task. The competitiveness of a national economy can be considered as one of the factors determining its investment attractiveness. In the paper to assess investment attractiveness, the results of the study on the competitiveness of world economies published by the World Economic Forum and the actual values of Japanese foreign investment were used. According to Guzik's proposals, an attractiveness rate was estimated and based on the value obtained from the reference models and the actual values for the data from the years 2006-2015. The results of the research include rankings of investment attractiveness.